2011
DOI: 10.1007/s11739-011-0671-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with polyunsaturated fatty acids in patients with heart failure

Abstract: Despite the clinical and prognostic improvement obtained with the current medical treatment, heart failure (HF) continues to have high morbidity and mortality and its prevalence is increasing in most regions of the world. Thus, there is a need for novel adjunctive therapies that act independently of current neurohormonally and haemodynamically oriented drugs. Nutritional approaches are particularly attractive because they could work additively with established therapies without negative hemodynamic effects. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 82 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…While recruitment was still ongoing, hospitalization for heart failure (HF) was added to the definition of MACE by protocol amendment. This modification was made due to increased focus on HF in the elderly, studies showing reduction in adverse left ventricular remodeling with n3-PUFA [19][20][21] , and potentially to increase statistical power of the trial. The primary safety outcome was serious bleeding, defined according to Bleeding Academic Research Consortium (BARC) criteria 22 .…”
Section: Discussionmentioning
confidence: 99%
“…While recruitment was still ongoing, hospitalization for heart failure (HF) was added to the definition of MACE by protocol amendment. This modification was made due to increased focus on HF in the elderly, studies showing reduction in adverse left ventricular remodeling with n3-PUFA [19][20][21] , and potentially to increase statistical power of the trial. The primary safety outcome was serious bleeding, defined according to Bleeding Academic Research Consortium (BARC) criteria 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that adults with cardiac problems might benefit from n -3 PUFA, as they prevent atrial fibrillation recurrence and increase left ventricle systolic function and functional capacity ( 68 , 69 ) . A dose-dependent benefit of n -3 PUFA, whereby a higher dose was more beneficial, was demonstrated in a small trial on patients with chronic heart failure ( 70 ) .…”
Section: Pufamentioning
confidence: 99%
“…Supplementation with natural compounds is discussed as an alternative for CD treatment (Jelicks et al, 2011;Maldonado et al, 2021). Literature indicates that omega-3 has important effects over treatment for cardiovascular diseases, reducing the occurrence of fatal events and hospital admissions (Nodari et al, 2011). A single-center double-blind clinical trial (clinicaltrials.gov #NCT01863576) was performed to investigate the effect of omega-3 supplementation in CCC patients.…”
Section: Natural Compoundsmentioning
confidence: 99%